We are wolves - Nannestad, Katrina (Atheneum Books for Young Readers, 2022)
When the Russian Army marches into East Prussia at the end of World War II, the Wolf family flees, but Liesl, Otto, and their baby sister Mia are separated from their mother and they are forced to do dangerous things in order to survive.--
A Caitlyn Dlouhy book
Originally published in Australia in 2020 by HarperCollinsChildren'sBooks
Keywords: Geschichte 1945; Geschwister; Flucht; Kriegswaise; Zweiter Weltkrieg; Osteuropa; Siblings / Juvenile fiction; Missing children / Juvenile fiction; Survival / Juvenile fiction; Refugees / Juvenile fiction; World War, 1939-1945 / Juvenile fiction; Germans / Lithuania / Juvenile fiction; Prussia, East (Poland and Russia) / Juvenile fiction; Lithuania / Juvenile fiction; Brothers and sisters / Fiction; Lost children / Fiction; Frères et surs / Romans, nouvelles, etc. pour la jeunesse; Enfants disparus / Romans, nouvelles, etc. pour la jeunesse; Habiletés de survie / Romans, nouvelles, etc. pour la jeunesse; Réfugiés / Romans, nouvelles, etc. pour la jeunesse; Guerre mondiale, 1939-1945 / Romans, nouvelles, etc. pour la jeunesse; Allemands / Lituanie / Romans, nouvelles, etc. pour la jeunesse; Kinderbuch